Permanent emergency: Inequality in access to hospitalisation among urban elderly Chinese. Issue 8 (3rd August 2018) - Liao, Tim F.; Wang, Cuntong
ABSTRACT: The phenomenon of elderly patients staying in hospital emergency department observation units for extended time in urban China poses a challenge to China's healthcare system and presents a social problem of inequality. In this paper, we analyse statistics collected from 16 major public hospitals in Beijing to assess the extent and intensity of the problem and examine interviews of medical professionals to understand the mechanisms linking the issue to the Chinese healthcare system. We study the issue with the literature on market transition theory and on China's recent healthcare reforms and view this age-based inequality as an outcome of the economic and social transformations in China. We make a few policy recommendations including using age-specific bed turnover and mortality rates for evaluating performance, employing three different release-status dependent mortality rates of emergency department patients for the evaluation of hospitals, and improving the capacity of post-acute, ambulatory care and geriatric care services in urban China.